An Analysis Of Circular Economy Implementation In Women-Led Msmes And/Or Social Enterprises - Damayanti, Liesda; Sofilda , Eleonora (Journal Research of Social Science, Economics, and Management, 2025)
This study aims to analyze the implementation of the circular economy within micro, small, and medium enterprises (MSMEs), as well as social entrepreneurship ventures led or owned by women. The circular economy is regarded as an alternative to the linear economic model in addressing the climate crisis and broader global sustainability challenges. In the context of Indonesia, MSMEs play a vital role in the national economy, with a significant proportion managed by women, thereby positioning them as key agents of change in advancing sustainable business models. This research adopts a descriptive qualitative approach, utilizing case studies and in-depth interviews with women-led MSMEs and social entrepreneurs engaged in circular business practices. The analysis employs the 9R framework and the ReSOLVE framework to assess the level of circularity implementation. Additionally, it incorporates a gendered leadership behavior framework to identify the leadership styles and enabling factors essential for accelerating the transition toward a circular economy. The findings reveal that while circular economy initiatives are emerging, entrepreneurs face several barriers, including consumer behavior preferences, limited knowledge, regulatory support gaps, supply chain collaboration issues, and organizational constraints—particularly the lack of skills, expertise, and technological capacity required for holistic implementation. Nonetheless, women's leadership—characterized by collaboration, participation, and value-driven approaches—facilitates the integration of social and environmental dimensions into circular business practices. This study proposes a gender-sensitive and sustainable circular economy business model for MSMEs and social enterprises, advocating for an inclusive, phased, and context-based transition strategy.